2023
DOI: 10.1001/jamaneurol.2023.3400
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam vs Lamotrigine as First-Line Antiseizure Medication in Female Patients With Idiopathic Generalized Epilepsy

Emanuele Cerulli Irelli,
Enrico Cocchi,
Alessandra Morano
et al.

Abstract: ImportanceAfter the recent limitations to prescribing valproate, many studies have highlighted the challenging management of female patients of reproductive age with idiopathic generalized epilepsy (IGE). However, no study, to the authors’ knowledge, has addressed the comparative effectiveness of alternative antiseizure medications (ASMs) in these patients.ObjectiveTo compare the effectiveness and safety of levetiracetam and lamotrigine as initial monotherapy in female patients of childbearing age with IGE.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Lamotrigine (LTG) is an old ASM which inhibits the release of the excitatory neurotransmitters via blocking voltage-sensitive sodium channels ( 56 ). A RCT suggested that it was a better choice for the treatment of focal epilepsy than LEV ( 57 , 58 ). Compared to LCM, LTG may have additional effects on calcium channels and therefore is more likely to cause arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine (LTG) is an old ASM which inhibits the release of the excitatory neurotransmitters via blocking voltage-sensitive sodium channels ( 56 ). A RCT suggested that it was a better choice for the treatment of focal epilepsy than LEV ( 57 , 58 ). Compared to LCM, LTG may have additional effects on calcium channels and therefore is more likely to cause arrhythmias.…”
Section: Discussionmentioning
confidence: 99%